Computational studies of mechanisms underlying the reactions of enzymatic and nonenzymatic systems - Xu, Kai (2017)
Computational chemistry has been proven to be increasingly helpful and thus important when investigating chemical properties such as chemical reactivity. The hybrid quantum mechanics and molecular mechanics (QM/MM) method that exploits the advantages of both quantum mechanics (QM) and molecular mechanics (MM) methods is a promising tool to gain detailed insights into complex systems such as enzymes and metal-organic frameworks (MOFs). Herein, QM/MM calculations are applied to three enzyme systems (cytochrome P450 Family 19 Subfamily A Member 1 (CYP19A1), heme oxygenase (HO), and Mo-Cu carbon monoxide dehydrogenase (MoCu CODH)) and one MOF (Cu-PDW) system, to elucidate the reaction mechanisms involved therein. For CYP19A1, the substrate was found able to act as proton source in the second step and Cpd I-driven mechanisms for the third step that well explain latest experimental observations were proposed. Ferric superoxide was found as a likely reactive species for ferric verdoheme formation in HO in the absence of a reducing equivalent and the reaction mechanism was also studied. For Mo-Cu CODH, the release of CO2 from its thiocarbonate intermediate, which was energetically difficult in DFT calculations, was found plausible in our QM/MM calculations, implying the importance of the protein environment. For the Cu-PDW MOF, CH-π interactions between substrates and the organic ligand in the MOF were identified as a key factor that leads to the enatioselectivity in the reaction studied. The mechanistic scenarios derived could provide guidelines for the development of drugs targeting CYP19A1, the engineering of the aforementioned enzymes, and the design of more efficient Cu-PDW MOFs.